Intra- and inter-rater reliability of the Knee Society Knee Score when used by two physiotherapists in patients post total knee arthroplasty - S. Gopal; W. Wood; H. Myezwa; A. Stewart (AOSIS, 2010)
Background and Purpose: It has yet to be shown whether routine physiotherapy plays a role in the rehabilitation of patients post totalknee arthroplasty (Rajan et al 2004). Physiotherapists should be using validoutcome measures to provide evidence of the benefit of their intervention. The aim of this study was to establish the intra and inter-rater reliability of the Knee Society Knee Score, a scoring system developed by Insall et al(1989). The Knee Society Knee Score can be used to assess the integrity of theknee joint of patients undergoing total knee arthroplasty. Since the scoreinvolves clinical testing, the intra-rater reliability of the clinician should be established prior to using the scores as datain clinical research. W here multiple clinicians are involved, inter-rater reliability should also be established.Design: This was a correlation study.Subjects: A  sample of thirty patients post total knee arthroplasty attending the arthroplasty clinic at Johannesburg Hospital between six weeks and twelve months postoperatively.M ethod: Recruited patients were evaluated twice with a time interval of one hour between each assessment. Statistical A nalysis: The intra- and inter-rater reliability were estimated using Intraclass Correlation Coefficient (ICC). R esults: The intra-rater reliability showed excellent reliability (h= 0.95) for Examiner A  and good reliability (h= 0.71)for Examiner B. The inter-rater reliability showed moderate reliability (h= 0.67 during test one and h= 0.66 during test two).Conclusion: The KSKS has good intra-rater reliability when tested within a period of one hour. The KSKS demonstrated moderate agreement for inter rater reliability.